2019
DOI: 10.1177/2050313x19893580
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Crohn’s disease identified in a patient being treated with secukinumab: A case report

Abstract: IL-17 antagonism is among the most potent treatments for psoriasis. Generally safe, new onset and exacerbations of inflammatory bowel disease may occur in association with IL-17 therapy. We describe a patient with long-standing history of psoriasis and psoriatic arthritis in whom asymptomatic Crohn’s disease was identified during treatment with secukinumab. The patient underwent an elective colonoscopy for colorectal cancer screening which revealed inflammation and multiple ulcers in the terminal ileum suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…A total of 29 studies were identified in the published literature, including 25 case reports ( Ehrlich et al, 2018 ; Grimaux et al, 2018 ; Paul et al, 2018 ; Wang et al, 2018 ; Achufusi et al, 2019 ; Grossberg, 2019 ; Haidari et al, 2019 ; Johnston and Veettil, 2019 ; Philipose et al, 2019 ; Rodriguez et al, 2019 ; Shimizu et al, 2019 ; Smith et al, 2019 ; Darch et al, 2020 ; Fieldhouse et al, 2020 ; Marin et al, 2020 ; Merino Gallego et al, 2020 ; Nazarian et al, 2020 ; Ali et al, 2021 ; Mu et al, 2021 ; Obeidat and Murakami, 2021 ; Ma et al, 2022 ; Sykaras et al, 2022 ; Kukol et al, 2019 ; Nallapeta et al, 2019 ; Sethi et al, 2019 ) and 4 case series ( Fobelo et al, 2018 ; Shukla et al, 2018 ; Vernero et al, 2019 ; Lee et al, 2020 ); a total of 34 cases raised evidence of IBD occurrence during therapy with SEC (27 cases, 79.4%) and IXE (7 cases, 20.6%). Characteristics of the included cases are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 studies were identified in the published literature, including 25 case reports ( Ehrlich et al, 2018 ; Grimaux et al, 2018 ; Paul et al, 2018 ; Wang et al, 2018 ; Achufusi et al, 2019 ; Grossberg, 2019 ; Haidari et al, 2019 ; Johnston and Veettil, 2019 ; Philipose et al, 2019 ; Rodriguez et al, 2019 ; Shimizu et al, 2019 ; Smith et al, 2019 ; Darch et al, 2020 ; Fieldhouse et al, 2020 ; Marin et al, 2020 ; Merino Gallego et al, 2020 ; Nazarian et al, 2020 ; Ali et al, 2021 ; Mu et al, 2021 ; Obeidat and Murakami, 2021 ; Ma et al, 2022 ; Sykaras et al, 2022 ; Kukol et al, 2019 ; Nallapeta et al, 2019 ; Sethi et al, 2019 ) and 4 case series ( Fobelo et al, 2018 ; Shukla et al, 2018 ; Vernero et al, 2019 ; Lee et al, 2020 ); a total of 34 cases raised evidence of IBD occurrence during therapy with SEC (27 cases, 79.4%) and IXE (7 cases, 20.6%). Characteristics of the included cases are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In a phase 2 randomized clinical trial of another anti‐IL‐17 agent, brodalumab, CD worsening was also detected at a higher rate in the anti‐IL‐17 treatment group compared with the placebo group (25.0% vs. 6.3%), leading to the early termination of the study 13,14 . In addition to the clinical trial on secukinumab multiple case reports have emerged reporting patients who developed IBD while on secukinumab 3,6,15–18 . Many of them had family histories or previous symptoms of IBD further supporting the role of genetic polymorphism 3,6,17,18 …”
Section: Discussionmentioning
confidence: 99%
“…13,14 In addition to the clinical trial on secukinumab multiple case reports have emerged reporting patients who developed IBD while on secukinumab. 3,6,[15][16][17][18] Many of them had family histories F I G U R E 1 Colonoscopy photos from baseline colonoscopy with diverticulosis in descending and sigmoid colon, otherwise normal. Sigmoidoscopy photos after patient treated with secukinumab (postsecukinumab) showing ulcerated and edematous mucosa in sigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between IL-17 inhibitors and the potential risk of IBD exacerbation was also documented in several case reports. Haidari et al reported a case of asymptomatic CD in patients with psoriasis following secukinumab treatment [114]. Johnston and Veettil presented a case of a patient with psoriasis who developed UC during treatment initiation with secukinumab [115].…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%